Cardiopulmonary Response to Exercise Testing in People with Chronic Stroke: A Retrospective Study - Sandra A. Billinger; Jordan M. Taylor; Barbara M. Quaney (Stroke Research and Treatment)
Background and Purpose. This study investigated the cardiopulmonary response and safety of exercise testing at peak effort in people during the chronic stage of stroke recovery. Methods. This retrospective study examined data from 62 individuals with chronic stroke (males: 32; mean (SD); age: (12.0) yr) participating in an exercise test. Results. Both males and females had low cardiorespiratory fitness levels. No significant differences were found between gender for peak HR (𝑃=0.27), or VO2 peak (𝑃=0.29). Males demonstrated higher values for minute ventilation, tidal volume, and respiratory exchange ratio. No major adverse events were observed in the exercise tests conducted. Discussion and Conclusion. There are differences between gender that may play a role in exercise testing performance and should be considered when developing exercise programs. The low VO2 peak of this cohort of chronic stroke survivors suggests the need for participation in exercise interventions.